SERS-encoded nanocomposites for dual pathogen bioassay. (15th April 2020) - Shan, Yaqi; Wang, Mingliang; Shi, Zengliang; Lei, Milan; Wang, Xiaoxuan; Wu, Fu-Gen; Ran, Huan-Huan; Arumugam, Gowri Manohari; Cui, Qiannan; Xu, Chunxiang
Abstract: Surface-enhanced Raman spectroscopy (SERS) has been successfully applied to detect various biomolecules, but it is still in challenge to assay living cells or bacteria sensitively, selectively and quantitatively in complex environments. In this paper, 4-ATP and DTNB are assembled on Ag nanoparticle (NP) -decorated poly (styrene-co-acrylic acid) (PSA) nanospheres and then sealed by silica shells to form sensitive SERS labels based on the localized surface plasmon resonance of Ag NPs and large light scattering cross-sections of PSA nanospheres. They are further developed as encoding tags for dual detection of S. aureus and E. coli after assembling corresponding aptamers, which demonstrate ultralow detection limits of 8 cell L −1 for S. aureus and 2 cell L -1 for E. coli . Such a bioassay indicates a point-of-care strategy of ultrasensitively biomedical detections by encoding specific SERS tags.